A simple assessment of haemothoraces thickness predicts abundant transfusion: A series of 525 blunt trauma patients. Issue 1 (January 2015) - Gignon, Lucile; Charbit, Jonathan; Maury, Camille; Latry, Pascal; Taourel, Patrice; Millet, Ingrid; Capdevila, Xavier
Abstract: Background: The goal of this study was to evaluate the performance of haemothorax quantification to predict an abundant transfusion in blunt thoracic trauma patients. Methods: This study included all severe trauma patients admitted into our trauma centre from January 2005 to January 2010, who presented a blunt thoracic trauma (thoracic AIS ≥1) and had a CT scan within the first hour following admission. For each haemothorax, thickness of dominant side and the cumulated thicknesses of both sides (Dominant- t, Cumulated- t ), as well as lengths (Dominant- l, Cumulated- l ) and the calculated volumes (Dominant- v, Cumulated- v provided by a previously validated formula) were retrospectively measured by CT scan. A multiple logistic regression was performed to define the independent risk factors for an abundant transfusion (≥5 packed red blood cells in the first 24 h). Finally, ROC curves have been drawn on an isolated thoracic trauma subgroup to predict abundant transfusion. The more specific cut-offs were extracted from this analysis. Results: From the 525 blunt thoracic trauma patients (75% males, mean age 38.2 (SD18.7) years, mean ISS 22.5 (SD16.4)), 31% received an abundant transfusion. In multivariable analysis, Cumulated- t was significantly associated with an abundant transfusion (OR 1.3 [95% CI 1.1–1.4], P = 0.002). In isolated thoracic trauma subgroup ( n = 251), the global abilities of different CT measurements to predict abundant transfusion were significantly comparable (AUCs 0.69–0.70). The more specific cut-offs were established at 28 mm for Cumulated- t (specificity 92%, positive predictive value 47%) and at 24 mm for Dominant- t (specificity 92%; positive predictive value 43%). Conclusion: The haemothorax quantification upon admission may help to predict transfusion needs. Cumulated- t was found independent risk factor for abundant transfusion in a large population of severe trauma patients. Beyond a Cumulated- t of 28 mm or a Dominant- t of 24 mm, abundant transfusion will be very frequently necessary. Level of evidence: Retrospective review, level III.